Jordan : Fifth Review Under the Stand-By Arrangement, Request for Waivers of Nonobservance of Performance Criterion and Applicability of Performance Criterion, Modification of Performance Criterion, and Rephasing of Access. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Jordan's Fifth Review Under the Stand-by Arrangement, Request for Waivers of Nonobservance of Performance Criterion (PC) and Applicability of PC, Modification of PC, and Rephasing of Access. Program performance in 2014 is broadly on track. The end-September PC on the central government primary deficit is estimated to have been met, but the PC on the combined public sector deficit is likely to have been missed owing to a shortfall in gas flows from Egypt. International reserves continued to over-perform through September. The IMF staff supports the completion of the fifth review and the related purchase.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet